2001
DOI: 10.1097/00004356-200112000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Struck by stroke: A pilot study exploring quality of life and coping patterns in younger patients and spouses

Abstract: So far, research on quality of life after stroke has focused mainly on elderly patients. This study is targeted at younger stroke patients and their partners, aiming to evaluate stroke impact, as related to coping strategy. For our pilot study, eight patients who had suffered a stroke and four partners completed the Impact of Event Scale questionnaire. The mean age was 47.6 years in patients and 44.5 years in partners. The patients' level of activities of daily life was assessed using the Barthel Index. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Thus it is the opposites of these strategies, rigid adherence (for example, being unable to switch to a more interpersonal version of good sex once the initial excitement of a long term relationship begins to wane) and helplessness (for example, feeling that one's sexual problems will never be cured) that are associated with less successful coping. However, where the stressful event is irreversible (such as loss of erectile function following prostate surgery) and circumstances cannot be changed, accommodative strategies are associated with better quality of life for both patients and partners (Smout, Koudstaal, Ribbers, Janssen, & Passchier, 2001;Boerner, 2004). Thus, it seems likely that as individuals age, accommodative strategies will become increasingly important where irreversible physiological difficulties increasingly impose constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is the opposites of these strategies, rigid adherence (for example, being unable to switch to a more interpersonal version of good sex once the initial excitement of a long term relationship begins to wane) and helplessness (for example, feeling that one's sexual problems will never be cured) that are associated with less successful coping. However, where the stressful event is irreversible (such as loss of erectile function following prostate surgery) and circumstances cannot be changed, accommodative strategies are associated with better quality of life for both patients and partners (Smout, Koudstaal, Ribbers, Janssen, & Passchier, 2001;Boerner, 2004). Thus, it seems likely that as individuals age, accommodative strategies will become increasingly important where irreversible physiological difficulties increasingly impose constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems likely that as individuals age, accommodative strategies will become increasingly important where irreversible physiological difficulties increasingly impose constraints. Indeed, it has been shown that flexibility tends to increase with age whilst tenacity declines (Smout et al, 2001). This helps explain why the decline in sexual function with age among women is not accompanied by an increase in distress (Hayes & Dennerstein, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores on one of the subscales indicates more use of that attitude [30]. The Dutch translation of this questionnaire [31] has previously been used in a stroke population [32,33]. We adjusted the wording for stroke patients by rephrasing certain difficult sentences.…”
Section: Methodsmentioning
confidence: 99%
“…In health related studies, it has been used in people suffering from peptic ulcer disease and irritable bowel disease (18), osteoarthritis (19), AIDS (20), cancer (21,22), cystic fibrosis (23), stroke (24), multiple sclerosis (17), mental illness (25), amyotrophic lateral sclerosis (26,27), people with leukaemia and lymphoma (28), people with End Stage Renal Failure (29), carers of people with dementia (30), and young people with diabetes (31) to name a few.…”
Section: Introductionmentioning
confidence: 99%